State history. Native Americans. Chiefs. 1935-12-31 - Browne, F. C. (1935)
Pioneer Washingtonia. / by F. C. Browne. First river pilot on the Columbia was chief Com-Com-ly, greatest of early Columbia river chieftains. From his lookout high upon a hillside he would watch for the arrival of a Hudson's Bay ship, and when one came in sight he would don his Hudson's Bay uniform and order twenty of his slaves to launch the royal canoe which took him out to the vessel.